Utilization of remote sensing techniques for the quantification of fire behavior in two pine stands. (July 2017) - Mueller, Eric V.; Skowronski, Nicholas; Clark, Kenneth; Gallagher, Michael; Kremens, Robert; Thomas, Jan C.; El Houssami, Mohamad; Filkov, Alexander; Hadden, Rory M.; Mell, William; Simeoni, Albert
Abstract: Quantification of field-scale fire behavior is necessary to improve the current scientific understanding of wildland fires and to develop and test relevant, physics-based models. In particular, detailed descriptions of individual fires are required, for which the available literature is limited. In this work, two such field-scale experiments, carried out in pine stands under mild conditions, are presented. A particular focus was placed on non-intrusive measurement, as the capabilities of advanced remote sensing techniques, along with more traditional approaches, are explored. A description of the fires is presented, with spread occurring predominantly in the surface fuels with intensities in the range of 200–4400 kW m -1, and punctuated by isolated regions of crown fire. The occurrence of crown fire is investigated and linked to regions of greater canopy density, and it is found that the total fire intensity may increase locally to as much as 21, 000 kW m -1 . The light winds do not appear to play a direct role in the changes in fire behavior, while fuel structure may be important. The measurements described herein provided a reasonable overall description of the fires, however, the current resolution (both spatial and temporal) falls short of definitively explaining some transitional aspects of the fire behavior, and future improvements are suggested.